2017
DOI: 10.3390/f8050173
|View full text |Cite
|
Sign up to set email alerts
|

Earlywood and Latewood Widths of Picea chihuahuana Show Contrasting Sensitivity to Seasonal Climate

Abstract: Abstract:The existence of endangered tree species in Mexico necessitates an understanding of their vulnerability to the predicted climate changes (warming and drying trends). In this study, the sensitivity to climate of earlywood (EW) and latewood (LW) widths of the threatened Picea chihuahuana was determined. The response of EW and LW to climate variables (maximum temperature, minimum temperature, precipitation, evaporation, and a drought index) was analyzed by means of correlation analysis using dendrochrono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 39 publications
4
7
1
1
Order By: Relevance
“…By extracting information at the intra-annual scale, we have exponentially expanded the range of studies that can be accomplished using tree rings, including the expansion of tree ring’s temporal resolution to season or even month (Cabral-Alemán et al, 2017), a better understanding of tree-physiology (Bouriaud et al, 2005), and the discovery of stronger proxies for environmental parameters (Babst et al, 2016; Dannenberg and Wise, 2016; Griffin et al, 2013). For example, tropical trees, previously a quandary for dendrochronological research (see the ‘Low latitudes’ section), are now analyzed via anatomy (Venegas-González et al, 2015) for climate-specific signatures and the effects of climate change (Adams et al, 2017; Castagneri et al, 2015; Ziaco et al, 2016).…”
Section: Wood Anatomymentioning
confidence: 99%
“…By extracting information at the intra-annual scale, we have exponentially expanded the range of studies that can be accomplished using tree rings, including the expansion of tree ring’s temporal resolution to season or even month (Cabral-Alemán et al, 2017), a better understanding of tree-physiology (Bouriaud et al, 2005), and the discovery of stronger proxies for environmental parameters (Babst et al, 2016; Dannenberg and Wise, 2016; Griffin et al, 2013). For example, tropical trees, previously a quandary for dendrochronological research (see the ‘Low latitudes’ section), are now analyzed via anatomy (Venegas-González et al, 2015) for climate-specific signatures and the effects of climate change (Adams et al, 2017; Castagneri et al, 2015; Ziaco et al, 2016).…”
Section: Wood Anatomymentioning
confidence: 99%
“…To complement the understanding of the dynamics of radial growth in response to drought, a better temporal resolution of tree-ring proxies is required (Timofeeva et al 2017 ). In conifers, the measurement of earlywood and latewood widths is often used to study seasonal growth responses to climate and drought (e.g., Griffin et al 2011 , 2013 ; Cabral-Alemán et al 2017 ; Camarero et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Dong et al [16] found that high winter temperatures in the previous year had an important impact on the tree growth of Chinese cedar (Cryptomeria fortune) in Fujian province of humid subtropical China. The dendroecological study of Chihuahua spruce (Picea chihuahuana) in northern Mexico also showed that cool and wet conditions in the previous winter could favor the earlywood and latewood growth of the current year [17]. In addition, the current August to October temperature also had positive impacts on the tree growth of T. longibracteata at the MRS site (p < 0.05, Figure 5a), reflecting the positive effect of temperature on photosynthesis, wood formation duration, and tree growth [51].…”
Section: Previous Growing Season Temperature Reconstructionmentioning
confidence: 99%